Believe is not a propositional attitude verb - Wimmer, Simon (Proceedings of the Amsterdam Colloquium, 2024)
I develop a challenge for the view that believe is a propositional attitude verb based on two observations: (i) believe can embed in O, and (ii) in O does not denote a proposition. To develop my challenge, I argue (section 2) that believe is not homonymous or polysemous between a propositional belief-that and non-propositional belief-in interpretation, and (section 3) that type-shifting in O’s denotation to a proposition falsely predicts that belief-in and belief-that reports are equivalent.